Plastic tools for aircraft production - Digby, Paul K.; Paul, Walter J.; Connolly, J. V. (College of Aeronautics, Cranfield, 1955)
The most important current problem associated with aircraft production is the necessity for a reduction in the time cycle from design to completion of the first production machine. Tool manufacture is one aspect in which improvement is desirable. The use of thermo- and setting-plastics for drop-hammer and double-curvature panel drill jigs is examined aver a wide technical and economic field, in order to establish a sound foundation for investigating the suitability of plastics for tooling. Tools were designed to isolate the variable parameters and a study of their behaviour has commenced , dth the assistance of high-speed filming, to ascertain the limitations of the various materials. Casting resins are preferable for both punches and dies although the laminated form, in addition to being the better type for pcnel drill jigs, appears to be the most satisfactory die material available at present. It was concluded that plastics facilitate easier and cheaper tool production titan is practicable with zinc and, for the tools produced, reduce the necessary time cycle of production by about 80 per cent with a corresponding reduction in the man.- hours required. In the tests made to develop suitable plastic tools, attention was concentrated on the development of a suitable slightly flexible punch, and a rigid diet following the most promising indications of this work. It was found that Tenite Medium Bard was a good punch material with a life of over 1,000 components, the springback differing from that of a Kayen Alloy punch by less than one degree for all the tool shapes tested. The economic savings are approximately cost 87 per cent, man-hours 84 per cent, and time cycle 81 per cent. It should. be noted that the ;lunch and die selected for this test was a severe forming case of a double curvature bead. The most satisfactory die developed was manufactured from Aralditc D resin, glass fibre and french chalk. Limited tests with a Tenite M.H. punch gave satisfactory results for short runs, and in all probability longer runs could be made. The economic reductions effected were; cost, 68.5 per cent and man-hours, 86 per cent.